CDR 2019
DOI: 10.20517/cdr.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

The effects of growth hormone on therapy resistance in cancer

Abstract: Pituitary derived and peripherally produced growth hormone (GH) is a crucial mediator of longitudinal growth, organ development, metabolic regulation with tissue specific, sex specific, and age-dependent effects. GH and its cognate receptor (GHR) are expressed in several forms of cancer and have been validated as an anti-cancer target through a large body of in vitro, in vivo and epidemiological analyses. However, the underlying molecular mechanisms of GH action in cancer prognosis and therapeutic response had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 206 publications
(230 reference statements)
2
28
0
Order By: Relevance
“…Conversely, melanoma with dysfunctional melanosomal and melanogenic machinery have increased cisplatin sensitivity [27]. One of the most critical effects of the melanoma oncogene MITF is therefore in therapy resistance—a phenomenon in cancer cells which also strongly implicates GH action [14], especially in metastatic (stage IV) melanoma [21], which also displays the highest GHR expression in the NCI60 panel [6] of 60 human tumor cell lines of eleven different cancer types. Although the exogenous growth factors bFGF, EGF, and HGF have been found to not affect V600E-BRAF melanoma viability or response to BRAF-inhibitors [60], we have previously reported that GHR inhibition sensitizes human melanoma to the BRAF inhibitor vemurafenib by suppressing ABC-transporter-mediated clearance of vemurafenib [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, melanoma with dysfunctional melanosomal and melanogenic machinery have increased cisplatin sensitivity [27]. One of the most critical effects of the melanoma oncogene MITF is therefore in therapy resistance—a phenomenon in cancer cells which also strongly implicates GH action [14], especially in metastatic (stage IV) melanoma [21], which also displays the highest GHR expression in the NCI60 panel [6] of 60 human tumor cell lines of eleven different cancer types. Although the exogenous growth factors bFGF, EGF, and HGF have been found to not affect V600E-BRAF melanoma viability or response to BRAF-inhibitors [60], we have previously reported that GHR inhibition sensitizes human melanoma to the BRAF inhibitor vemurafenib by suppressing ABC-transporter-mediated clearance of vemurafenib [21].…”
Section: Discussionmentioning
confidence: 99%
“…Increased GH responsiveness was identified by immunohistochemical studies targeting GHR on melanoma patient-derived paraffin samples [11]. A large body of research in the last 20 years has implicated GH action in the regulation of multiple oncogenic processes such as proliferation, migration, invasion, anchorage-independent growth, as well as resistance to chemo- and targeted therapy in human tumors [12,13,14]. However, the essential molecular underpinnings of these GH-regulated oncogenic processes are only recently coming to light.…”
Section: Introductionmentioning
confidence: 99%
“…However, TME may modulate responses to cytotoxic therapy, and GH, as a part of TME, may contribute to this process. GH effects on therapy resistance to cancer has been well described (80). Here, we elaborate on additional aspects of GH actions contributing to its effects on treatment resistance.…”
Section: Gh Tme and Resistance To Therapymentioning
confidence: 94%
“…GH may also impact chemotherapy resistance via its effects on multi-drug efflux pumps, which transport xenobiotics out of the cytoplasm (80). For example, GH expression in four different human melanoma cell lines upregulated expression of multiple ABC-family multi-drug efflux pumps, rendering cells resistant to chemotherapy (84).…”
Section: Gh Tme and Resistance To Therapymentioning
confidence: 99%
“…A growing number of studies implicate GH also in development of therapeutic resistance in a variety of human cancers (322). Both JAK2-and Lyn-initiated pathways activate, upon anti-cancer treatment, many different systems that upregulate ABC-multidrug efflux pumps (ABCG2), block apoptosis, DNA repair (p53), and pro-apoptotic molecules (Bax, PPARg), suppresses caspase activation, and induce EMT and markers of stemness like ALDH1, NANOG, and CD24.…”
Section: Gh and Cancermentioning
confidence: 99%